(untitled) (Islamic Sciences Journal, 2025)
The practice of treating camels with tar to cure them of scabies was well-known among Arabs, and it is mentioned in several authenticated Hadiths (Prophetic traditions) and reports from the Companions and their followers. These Hadiths and reports reveal the existence of this disease among camels and its treatment. In this research, I have documented the Hadiths and reports related to this topic, followed by a study and analysis, and highlighted the insights that can be derived in the context of understanding the Prophetic Hadith